Czy francuska lodówka Dony Luizy Mendonçy działa(łaby) w Brazylii? - Jaworski, Jakub (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
Taking into account the Brazilian reception of the novel O Primo Bazilio, the author outlines the cultural connections between the Portuguese realist writer Eça de Queiroz and Brazil. The starting point of the argument is the heated public debate on the novel at the end of the 19th century. The article discusses Eça de Queiroz as a creative continuator of French realism and naturalism, referring to the specific cultural phenomena in Brazil and his unusual closeness with Romanticism. The article attempts to combine the musical narration of Eça and the irony present in his literary prose production and the new Brazilian cultural intertext. In the context of the mythical Pasiphae discourse as the story about an adulteress, Brazilian literature and music create a polyphonic narrative expression in so far as Eça´s discourse does the same. The poetic ending may be taken for a voice in the discussion about the position of a woman who does (not) liberate herself from the social convention in the patriarchal society.